(untitled) (CIPEEX, 2025)
This research seeks to demonstrate that testimonial evidence plays a dominant role in criminal justice and, therefore, this work aims to expose the fragility of memory, in order to promote critical reflection on the fallibility of testimonial evidence and deterministic judgments based solely on it. Through the method of bibliographical review, considering the analysis of doctrine and academic production on the topic, it will examine, beyond the domain of law, the concepts arising from neuroscience and the psychology of testimony. The results obtained confirm the discussions about the stages of memory formation and the main factors that produce memory contamination, comprising the most efficient methods of collecting testimonies. Therefore, it is necessary to further investigate false memories in criminal proceedings in order to obtain high-quality jurisdiction based on the assessment of the credibility of testimony.